Hedging Potential of Occupational and Regional Wage Indices - Schmal, Friederike; Trede, Mark Matthias (Journal of Income Distribution®, 2023)
This article suggests a readily implementable approach to hedging occupational and regional wage risks. We show that currently available administrative data of the German social security system can be aggregated into indices of occupational and regional wage levels. We define assets with payouts dependent on the occupational and/or regional wage development of a cohort. If such assets had been available in the past, annual and lifetime income inequality could have been reduced, and individual income volatility would have been smaller. By construction, there are no moral hazard problems, and the incentives to move jobs or regions are not affected. We conclude that introducing these hedging instruments could mitigate income shocks to some degree without case-by-case interference from politicians and without detrimental effects on labour allocation.